Strategi Kepala Sekolah Dalam Mengembangkan Life Skill Siswa di Madrasah Aliyah Roudlotul Banat Sidoarjo - Sohib Agil; M. Athoiful Fanan (EDUSIANA Jurnal Manajemen dan Pendidikan Islam, 2026)
This study explores the strategies employed by the principal in fostering students’ life skills at Madrasah Aliyah Roudlotul Banat Sidoarjo. The background of this research highlights the importance of life skills as essential competencies for students to face social changes and future challenges. In Islamic education, life skills also include moral and social values. The study is based on life skills education theory and educational leadership theory, emphasizing the role of principals in supporting holistic student development. This research uses a qualitative case study approach. Data were collected through interviews, observations, and documentation, and analyzed using thematic analysis. The findings reveal that the principal implements strategies such as integrating life skills into the curriculum, strengthening extracurricular activities, building a positive school culture, and collaborating with stakeholders. These strategies improve students’ independence, communication, and problem-solving skills. The study implies that effective leadership is essential in enhancing life skills education to better prepare students for future challenges.   Kata Kunci: Principal’s strategy; life skills; students; Madrasah Aliyah Roudlotul Banat; student empowerment